2021
DOI: 10.1002/jmd2.12212
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings of the posterior fossa in 47 patients with mucopolysaccharidoses: A cross‐sectional analysis

Abstract: Background Mucopolysaccharidoses (MPS) is a group of hereditary multisystemic lysosomal disorders. Most neuroimaging studies in MPS have focused on the supratentorial compartment and craniocervical junction abnormalities, and data regarding posterior fossa findings are scarce in the literature. Thus, our purpose is to describe posterior fossa findings on magnetic resonance imaging (MRI) of MPS patients. Methods We reviewed routine MRI scans of MPS patients being followed up at our institution (types I, II, III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…13 Three-fourth cases of MPS were reported to have normal or enlarged cerebellum, but other neuroimaging findings of enlarged perivascular spaces, cortical atrophy, white matter lesions, hydrocephalus, craniocervical junction abnormalities, and thickened middle cerebellar peduncles may be seen. 14 Patients with somatic mutations in PIK3CA are found to have increased brain cell growth causing MCAP and megalencephaly-polydactyly-polymicrogyria-hydrocephalus. Clinically, they have overgrowth of adipose, muscular, or skeletal tissue along with vascular malformations and epidermal nevus.…”
Section: Discussionmentioning
confidence: 99%
“…13 Three-fourth cases of MPS were reported to have normal or enlarged cerebellum, but other neuroimaging findings of enlarged perivascular spaces, cortical atrophy, white matter lesions, hydrocephalus, craniocervical junction abnormalities, and thickened middle cerebellar peduncles may be seen. 14 Patients with somatic mutations in PIK3CA are found to have increased brain cell growth causing MCAP and megalencephaly-polydactyly-polymicrogyria-hydrocephalus. Clinically, they have overgrowth of adipose, muscular, or skeletal tissue along with vascular malformations and epidermal nevus.…”
Section: Discussionmentioning
confidence: 99%
“…While some case reports have indicated the presence of diffuse high-intensity signal in the white matter of MPS IIIA and IIIB patients [23,24], other studies reported an absence of white-matter lesions in most MPS III cases [25].…”
Section: Introductionmentioning
confidence: 92%
“…Much less is known, however, about the white matter defects and, in particular, axonal pathology and demyelination in the MPS III patients. While some case reports have indicated the presence of diffuse high-intensity signal in the white matter of MPS IIIA and IIIB patients (Zafeiriou et al, 2001;Kara et al, 2008), other studies reported an absence of white-matter lesions in most MPS III cases (Reichert et al, 2021).…”
Section: Introductionmentioning
confidence: 92%